2014
DOI: 10.3998/ark.5550190.p008.597
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectroscopic characterization and DFT calculations of a new highly fluorescent heterocyclic system: imidazo[4,5-a]quinindoline

Abstract: New N-alkyl-substituted heterocyclic system imidazo [4,5-a]quinindolines (imidazo[4,5-f]-indolo[2,3-b]quinolines) were synthesized by one pot reaction of 1-alkyl-5-nitro-1H-benzimidazole with 2-(1-alkyl-1H-3-indolyl)acetonitrile in basic media via the nucleophilic substitution of hydrogen and concomitant cyclisation in good yields. Physical spectral (UV-vis, IR, NMR and fluorescence) and analytical data have established the structures of synthesized compounds. The fluorescence properties of these new heterocyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Other compounds as Isopropyl Myristate possess antioxidant and antibacterial properties (Faridha Begum et al, 2016). Furthermore, Rahman et al (2014) showed that 9-Hexadecenoic acid had antimicrobial properties.Several studies showed that Quinindoline had Antibacterial activity (Sokhanvar and Pordel, 2014;Pordel et al, 2016). Quinindolines are a group of synthetic analogs of the natural alkaloid neocryptolepine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other compounds as Isopropyl Myristate possess antioxidant and antibacterial properties (Faridha Begum et al, 2016). Furthermore, Rahman et al (2014) showed that 9-Hexadecenoic acid had antimicrobial properties.Several studies showed that Quinindoline had Antibacterial activity (Sokhanvar and Pordel, 2014;Pordel et al, 2016). Quinindolines are a group of synthetic analogs of the natural alkaloid neocryptolepine.…”
Section: Resultsmentioning
confidence: 99%
“…The quinindoline derivatives also revealed antimicrobial, antimuscarinic, antiviral, and cytotoxic potential. A combination of the quinindoline moiety with the imidazole nucleus may enhance optical and biological properties (Sokhanvar and Pordel., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In our earlier research works, some new fluorescent heterocyclic compounds have been synthesized with pentacyclic aromatic skeleton featuring indole, 4‐pyridinecarbonitrile, and benzimidazole or indazole systems as the key ingredients 33,34 . In the present study, which is conducted as continuation of our investigations on synthesizing new heterocyclic dyes as organic photosensitizers in DSSCs, 35,36 we have aimed at a synthesis of 3 H ‐benzofuro[2,3‐ b ]pyrazolo[4,3‐ f ]quinolines as novel fluorophores as high‐performance organic photosensitizers.…”
Section: Introductionmentioning
confidence: 99%